Detection Of Certain Virulence Attributes And Antimicrobial Resistance Pattern Among Clinical Isolates Of Acinetobacter Baumannii - GOPINATH PRAKASAM; S. GEETHAPRIYA; K. H. JAYAKEERTHANA; SRIVANI RAMESH (International Journal of Pharma and Bio Sciences, 2011)
Acinetobacter species are ubiquitous aerobic gram negative coccobacilli, emerging as an inevitable potential pathogen to establish its survival in the host environment and among debilitated patients by producing various extracellular virulence factors. A total of 46 clinical isolates of Acinetobacter baumannii were collected from different clinical specimens such as blood (14), pus (6), urine (4), sputum (4), endotracheal aspirate (12) and broncho alveolar lavage (6) and screened for the presence of invasive enzymes such as gelatinase, lecithinase and lipase. 21/46 isolates were positive for gelatinase, whereas 28 isolates showed strong positivity and 15 showed weak positivity for lipase. On the other hand, 40/46 isolates showed lecithinase activity by plate method while 10 were strong positive and 32 were weak positive by tube method. A higher percentage of clinical isolates was resistant to most of the routinely used antibiotics. 6.5% of isolates were found to be sensitive to ceftazidime, 10.8% to piperacillin-tazobactam , 23.9% to meropenem, 26% to gentamicin, 19.5% to ciprofloxacin and 39.1% to tetracycline.